Combination of imaging flow cytometry and time‐lapse microscopy for the study of label‐free morphology dynamics of hematopoietic cells. Issue 3 (1st March 2017) - Cosette, Jérémie; Moussy, Alice; Paldi, Andras; Stockholm, Daniel
Abstract: Cell differentiation is a longitudinal and dynamic process. Studying and quantifying such a process require tools combining precise time resolution and statistical power. Imaging flow cytometry (IFC) provides statistically significant number of microscopy images of individual cells in a sample at a given time point. Time‐lapse microscopy (TLM) is the method of choice for studying the dynamics of cell processes at a high temporal, but low statistical resolution. In this work, we show that the dynamic changes of cord‐blood derived CD34+ cells in response to cytokine stimulation can be successfully studied, in a label‐free way, by the combination of the IFCs statistical power and the TLM's high time resolution. Cell morphology phenotypes were quantified through roundness and surface area, measured both in IFC and with a homemade segmentation algorithm in TLM. Two distinct morphologies—polarized and round—were observed in cord‐blood derived CD34+. We show that some cells have the ability to fluctuate between these morphologies, suggesting that the apparent stable composition of round and polarized cells may actually represent a dynamic equilibrium. This example demonstrates that the different resolutions and modalities of IFC and TLM are complementary and allow the study of complex dynamic biological processes. © 2017 International Society for Advancement of Cytometry